2022
DOI: 10.3389/feart.2022.848247
|View full text |Cite
|
Sign up to set email alerts
|

Pore Characterization of Pyrite in the Longmaxi Formation Shale in the Upper Yangtze Area of China

Abstract: Pyrite is widely distributed in the Longmaxi marine shale in the Upper Yangtze area of China. Pyrite, one of the important components of shale, has an important influence on the enrichment of shale gas. However, there are currently only a few studies on this topic. Based on shale samples from drilling cores using field emission scanning electron microscopy, the pore characteristics of pyrite from the Longmaxi Formation in the Upper Yangtze area of China are studied. The results showed that the intergranular po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…18 Chen demonstrated that the pores within the pyrite framboids, which were as high as 5.66%, had a favorable contribution to the pore system of shale reservoir, and these pores could reserve free gas and promote gas enrichment. 19 In addition, the presence of pyrite in shale reservoirs can accelerate the oxidation of shale. A previous study indicated that most fracturing fluids contained dissolved oxygen (9 mg/L) and some oxidants, which were used as glue-breaking agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Chen demonstrated that the pores within the pyrite framboids, which were as high as 5.66%, had a favorable contribution to the pore system of shale reservoir, and these pores could reserve free gas and promote gas enrichment. 19 In addition, the presence of pyrite in shale reservoirs can accelerate the oxidation of shale. A previous study indicated that most fracturing fluids contained dissolved oxygen (9 mg/L) and some oxidants, which were used as glue-breaking agents.…”
Section: Introductionmentioning
confidence: 99%
“…It has been illustrated that pyrite has positive correlations with liquid hydrocarbon and total organic carbon (TOC), and it can promote the pyrolysis of organic matter and catalyze hydrocarbon generation . Chen demonstrated that the pores within the pyrite framboids, which were as high as 5.66%, had a favorable contribution to the pore system of shale reservoir, and these pores could reserve free gas and promote gas enrichment . In addition, the presence of pyrite in shale reservoirs can accelerate the oxidation of shale.…”
Section: Introductionmentioning
confidence: 99%